Toxicidade aguda e subcrônica de extratos de Pinus sp. em Zebrafish - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The presence of parasites in aquaculture systems is an obstacle to expanding the aquaculture production chain, causing losses and resulting in difficulties in treatment, due to the lack of proven efficient products. Among these parasites, the most commonly found is Lernea (Lernaea cyprinacea). As a possible alternative, the use of products of natural origin, such as plant extracts, is presented. Among them, the use of extracts from Pinus sp. was evaluated in vitro for its antiparasitic, antioxidant and anti-inflammatory potential, showing promising results. However, it is still necessary to quantify the toxicological effects in fish. Therefore, the objective of this work was to evaluate the toxicity of the aqueous extract of Pinus sp. in zebrafish (Danio rerio). Initially, 120 zebrafish specimens were exposed to concentrations of 0 (control), 50 mg/L and 100 mg/L of aqueous extract of Pinus sp. (4 replications per treatment; 10 fish per experimental unit) for 96 hours. Afterwards, a prolonged exposure experiment was carried out, lasting 28 days with exposure to concentrations of 0 (control), 1.0, 3.2, 10, 32 and 100 mg/L of aqueous extract, using 240 fish (4 repetitions per treatment; 10 fish per experimental unit). In both trials, mortality and the occurrence of physical and behavioral anomalies were observed. At the end of the prolonged exposure experiment, the fish were euthanized to collect samples of liver, muscle, gills and whole fish to quantify superoxide dismutase (SOD) activity, catalase (CAT) activity, protein carbonyl (PC) concentration and TBARS. During both experiments, no mortality occurred and no external or behavioral anomalies were observed. In the prolonged exposure test, dose-dependent lipid peroxidation was observed in the liver and gills, in addition to dose-dependent inhibition of SOD and CAT enzymes, indicating that the aqueous extract of Pinus sp. can cause cellular damage when used in doses above 3.2 mg/L.
Acute and subchronic toxicity of extracts of Pinus sp. in Zebrafish juveniles
Keywords: Nutrição animal; Aquicultura; Peptídeo bioativo; Animal nutrition; Aquaculture; Bioactive peptide; CNPQ::CIENCIAS AGRARIAS